Tracking what went where across toddlerhood: Feature‐location bound object representations in 2‐ to 3‐year‐olds' working memory. Issue 6 (18th June 2022) - Kibbe, Melissa M.; Applin, Jessica B.
Abstract: Two experiments examined the development of the ability to encode, maintain, and update integrated representations of occluded objects' locations and featural identities in working memory across toddlerhood. Sixty‐eight 28‐ to 40‐month‐old US toddlers (13 Asian or Pacific Islander, 6 Black, 48 White, 1 multiracial; 40 girls; tested between February 2015 and July 2017) tracked the locations of different color beads that were hidden simultaneously (Experiment 1) or sequentially (Experiment 2). Toddlers' ability to reliably store feature‐location bound object representations in working memory varied as a function of age, memory load, and task demands. These results bridge a developmental gap between infancy and early childhood and provide new insights into sources of limitation and developmental change in children's early object representational capacities.